Critical Discourse of Discursive Pluralism and Inclusivism of Islamic Leadership in the Local-National Context - Khirjan Nahdi; Muhamad Juaini; Hamzani Wathoni; Danang Prio Utomo; Muhammad Sururuddin; Aswasulasikin; Samsul Lutfi; Muh. Fahrurozi; Muh. Taufiq (CV. Literasi Indonesia, 2021)
This study aims to find the value of pluralism and inclusivism in the discursive leadership of Islam. The data was collected through the recording of documents from the discursive leader of the Islamic organization Nahdlatul Wathan (abbreviated NW), as well as the governor of West Nusa Tenggara (NTB abbreviated), Indonesia, namely Mr. Guru Bajang (abbreviated as TGB). Data is in the form of thought texts, statements, TGB actions, and other parties' statements as discursive. TGB is positioned as a discursive storyteller as well as a guide in its transformation. Data were analyzed according to the communication function in functional grammar and Critical Discourse Analysis component analysis. Through this study, it was found that the discretion of the TGB was related to optimism, alignment of Islamic values, safeguarding the Unitary Republic of Indonesia, caring for diversity, and building the nation as a discursive common property and needs as a plural society and transformed inclusively. As an ideational communication function, discursive becomes TGB aspirational form of contextual dynamism, as an instrument of accelerating interpersonal development agenda, and textual future historical responsibility. The five discursive TGB in this study belong and jointly guide the dynamics of the future. TGB as a storyteller has a reciprocal relation to the five discourses and has shown results through development progress in the context of NTB and Indonesia.